The role of GSTM1 gene polymorphism in pathophysiology, evaluation, and management of constipation of anorectal outlet obstruction - Wang, Shuo; Fan, Zhibin (Cellular and Molecular Biology, 2021)
Constipation of anorectal outlet obstruction may be caused by mechanical or functional causes. This complication is a debilitating disease that needs proper and timely treatment. Many studies have shown that there is a direct link between constipation and intestinal cancer. One of the most effective ways to prevent or diagnose intestinal cancer is through genetic studies. Evaluation of people's polymorphism shows how much they are at risk for cancer. Therefore, in this study, the GSTM1 gene polymorphism was evaluated in patients with constipation of anorectal outlet obstruction to assess better and manage this disease and investigate the possibility of anorectal cancer in these people. In this regard, 40 people with constipation of anorectal outlet obstruction were compared with 40 healthy people. In the case group (patients), in addition to demographic and clinical evaluations, the anorectal manometric test was used to diagnose the pathology of the disease. Results showed that out of 40 patients with constipation of anorectal outlet obstruction, 5 cases (12.5%) had megarectum, 7 cases (17.5%) had anismus, 10 cases (25%) had Hirschsprung's disease, 5 cases (12.5%) had descending perineum syndrome, 6 cases (15%) had rectal prolapse, 4 cases (10%) had enterocele, and 3 cases (7.5%) were with rectocele. Also, the results of GSTM1 gene deletion polymorphism showed that patients with constipation of anorectal outlet obstruction were almost two times more exposed to the null genotype than the control group (P <0.04). Therefore, in people with both constipation of anorectal outlet obstruction and null genotype (i.e., deletion in the GSTM1 gene), because they do not have glutathione-S transferase, they appear to be at higher risk for anorectal cancer than healthy people with the same genotype.